Metode Social Story dan Positive Reinforcement untuk Mengurangi Perilaku Tantrum pada Anak dengan Autisme - Frida Rufina Apriresti; Tiara Diah Sosialita (Jurnal Ners, 2025)
Tantrum behavior is one of the observable impacts in children with autism spectrum disorders. Previous studies have shown various benefits of implementing the social story method in children with autism spectrum disorders. The purpose of this study was to determine the benefits of the social story method when combined with positive reinforcement to reduce tantrum behavior in children with autism spectrum disorders. This study was a single case study with an A-B-A-B research design. The subject in this study was one kindergarten student and had been diagnosed with autism spectrum disorder from the results of the CARS Test or Childhood Autism Rating Scale. The results of this study indicate that the social story method combined with positive reinforcement is effective in reducing the frequency of tantrum behavior in the subject.